Thermo-mechanical properties of acrylated epoxidized hemp oil based biocomposites - Manthey, Nathan W. (2013)
In this study, novel acrylated epoxidized hemp oil bioresin was used in the manufacturing of jute fibre reinforced biocomposites. The 100% biocomposite laminates were characterised in terms of mechanical properties (tensile, flexural, Charpy impact and interlaminar shear), thermo-mechanical properties (glass transition temperature, storage modulus and crosslink density) and water absorption properties (saturation moisture level and diffusion coefficient). Comparisons with the equivalent synthetic vinylester resin based jute fibre reinforced biocomposite panels were performed. Scanning electron microscopic analysis confirmed panel samples containing acrylated epoxidized hemp oil to display improved fibre?matrix interfacial adhesion compared with the vinylester resin based samples. Furthermore in terms of mechanical properties acrylated epoxidized hemp oil based biocomposites compared favourably with those manufactured from vinylester resin synthetic resin. Dynamic mechanical analysis found acrylated epoxidized hemp oil based biocomposites to have lower glass transition temperature, storage modulus and crosslink density than vinylester resin based samples. Increasing acrylated epoxidized hemp oil content resulted in a marginal increase in saturation moisture content and diffusion coefficient.